Step-by-step explanation:
"b2" was replaced by "b^2". 1 more similar replacement(s).
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
a-((h*(b^2+b^2))/(2))=0
Simplify: hb2 /1
a - hb2 = 0
Factoring: a-hb2
Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)
(A+B) • (A-B) =
A2 - AB + BA - B2 =
A2 - AB + AB - B2 =
A2 - B2
AB = BA is the commutative property of multiplication.
- AB + AB equals zero and is therefore eliminated from the expression.
a1 is not a square
Binomial can not be factored as the difference of two perfect squares
a - hb2 = 0
Solve :a-hb2 = 0
I think